HUBUNGAN ASUPAN ENERGI, SERAT, DAN PENGELUARAN ENERGI DENGAN RASIO LINGKAR PINGGANG-PANGGUL (RLPP) - Hartanti, Dwi; Mulyati, Tatik (Universitas Islam Negeri Walisongo Semarang, 2017)
The enhancement of WHR value which is one of abdominal obesity predictor is usually correlated with the rise of chronic disease risks because its relations with the metabolic syndrome. Dietary intake and energy expenditure factors may have the important role of balance energy that can increase WHR value. The aim of this study is to analyze correlation of energy expenditure, energy and fiber intake with waist hip ratio (WHR) of officers. This cross-sectional study was taken place at PT. Pertamina (Persero) Semarang with consecutive counted 55 sample. Energy and fiber intake was estimated by dietary food record 2 x 24 hour dan Semi-Quantitative Food Frequency Quesionaire. While energy expenditure was counted by using form diary activity. Statistic correlation was calculated by Statistic Package for the Social Science (SPSS) for window. About 70,9% of total subject has abdominal obesity. The prevalence of abdominal obesity is higher in women (81,5%) than men (60,7%). The mean of energy intake is 2402.2 Â± 319.68 Kcal. Obese subject has 7,2% higher energy intake than normal subject. About 40% subject has light energy expenditure category and 45,5% subject is belong to moderate energy expenditure category. About 96,4% subject has fiber intake less than 25 gram per day. The result of this study shows that energy intake has association with WHR(r = 0.455 ; p = 0.000). Fiber intake is inversely associated with WHR(r = -0.382 ; p = 0.004). Energy expenditure also has negative association with WHR(r = -0.268 ; p = 0.048). There are significantly correlation of energy expenditure, energy and fiber intake with WHR.